2021
DOI: 10.1101/2021.03.17.435887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell cycle gene regulation dynamics revealed by RNA velocity and deep-learning

Abstract: The cell cycle is a fundamental process of life, however, a quantitative understanding of gene regulation dynamics in the context of the cell cycle is still far from complete. Single-cell RNA-sequencing (scRNA-seq) technology gives access to its dynamics without externally perturbing the cell. Here, we build a high-resolution map of the cell cycle transcriptome based on scRNA-seq and deep-learning. By generating scRNA-seq libraries with high depth, in mouse embryonic stem cells and human fibroblasts, we are ab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…2D). We confirmed an increase in expression of two major ABC transporters, including ABCB1, and ABCG2, and a decrease in PGR, another marker previously shown downregulated in the SP + compared to the SPof human myometrium cells (16) (37)(38)(39) were determined by the cell cycle score and the velocity of the scRNA-seq data, respectively. We identified a small group of cells within the vascular myocyte cluster in the G1/G0 phase (Fig 4A) using a computational assignment of cell-cycle stage, as described by Scialdone et al (40).…”
Section: Susd2supporting
confidence: 82%
See 1 more Smart Citation
“…2D). We confirmed an increase in expression of two major ABC transporters, including ABCB1, and ABCG2, and a decrease in PGR, another marker previously shown downregulated in the SP + compared to the SPof human myometrium cells (16) (37)(38)(39) were determined by the cell cycle score and the velocity of the scRNA-seq data, respectively. We identified a small group of cells within the vascular myocyte cluster in the G1/G0 phase (Fig 4A) using a computational assignment of cell-cycle stage, as described by Scialdone et al (40).…”
Section: Susd2supporting
confidence: 82%
“…Similar clusters were reported in a scRNA-seq comparison of fibroids and myometrium (36). The depth of sequencing for each cell was close to saturation allowing us to identify a small cell population with stem cell characteristics, including the expression of MSC markers SUSD2, MCAM, PDGFRβ, and CSPG4, a quiescent (G0) cell cycle state (37) and low transcriptomic activity/low RNA velocity (37)(38)(39). CRIP1 + /PECAM1cells were primarily located in the perivascular region, a known stem cell niche (42-44), particularly by the larger myometrial blood vessel.…”
Section: Discussionmentioning
confidence: 53%
“…Pebworth et al identified two transcriptional subtypes of IPCs; radial glia-like cells that express SOX2 and neuron-like cells that express neuronal genes like NEUROD6 ( 18 ). To explore these subtypes in cortical IPCs, we resolved the cell cycle trajectory for IPCs and early differentiating IPCs in samples from two donors (8.5 and 14 p.c.w) using DeepCycle ( 23 ), yielding a projection of each cell to an offset along the cell cycle. As predicted, RNA molecule counts (UMIs) increased gradually along the cell cycle, with a sudden drop at mitosis, corresponding to cell growth followed by cell division (Fig.…”
Section: Excitatory Lineage Of the Developing Neocortexmentioning
confidence: 99%
“…The majority of the computational tools used in this manuscript consisted of (v4.1.1), (v1.7.0), and (v2.3.1). We derived the cell-cycle genes for humans via Seurat::cc.genes, while we used the lists of human housekeeping genes 59 or mouse cell-cycling genes 60 from particular published work.…”
Section: Data Availabilitymentioning
confidence: 99%